Formative Assessment in a Geology Classroom: Promoting Learning by Giving Top Marks - Helman, Daniel S. (LPPM Universitas Negeri Jakarta, 2023)
Based on the observation that teacher expectation often drives classroom success, a project was undertaken whereby all students were given top marks in two sections of a geology classroom at the undergraduate level. To further this project, a student motivation strategy was attempted to take the place of their not having to fear for top marks. The results were sixfold: (1) the results of student work were well above average; (2) student work reflected teacher expectations; (3) student enthusiasm was well above average; (4) the instructor needed to use enthusiasm and humor to maintain discipline; (5) the instructor needed to parse the assignments so that the work would be done; (6) the administration was unhappy with the resulting data analytics. Based on this case study, one can confirm that student outcomes are highly dependent on teacher expectations and strategies; and that formative (not evaluative) assessments can be used effectively to raise the level of student learning.